Developing student character assessment questionnaire on French subject in state high schools - Nur Hamidah Assa'diyah; Samsul Hadi (Sekolah Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2021)
As time goes by, technological advances affect character crises, especially among students. This study is aimed at developing a student character assessment questionnaire for the French subject in state high schools of Yogyakarta Special Region. The study employed the 4D development formula comprising of Define, Design, Develop, and Disseminate. The study involved 269 students of X, XI, and XII grades as the samples. The reliability test was performed using the Cronbach’s Alpha formula, 0.689, with strong reliability. The validity of the study was tested using EFA (Exploratory Factor Analysis). The questionnaire used the Likert scale. The result of the study shows that 15 items are valid and can show the character of students in the French subject.